A study of unusual diamonds from the George Creek K1 Kimberlite dyke, Colorado - Chinn, Ingrid Lee (Department of Geological Sciences, 2014)
Cathodoluminescence photomicrographs of diamonds from the George Creek Kl (section 28) kimberlite dyke in Colorado reveal complex intergrowth relationships between CO?-free and CO?-bearing diamond growth generations. The distribution of the CO?-bearing diamond in some specimens suggests that this generation is younger than the CO?-free diamond growth generation, although the age relationships are mostly ambiguous. CO?-bearing diamond appears to have crystallized from fluids which invaded fractures and etched embayments in the CO?-free diamond growth generation, which shows evidence of plastic deformation. The CO?-free diamond growth generation commonly exhibits features caused by extreme plastic deformation during mantle residence time. Abundant yellow-green plastic slip planes transect zones of customary blue cathodoluminescence in many diamonds, and raised lamination lines have been recognized on resorption surfaces. The complexity and intensity of surface etch features in most George Creek diamonds, including the CO?-bearing growth generation, suggests that the diamonds were subjected to multiple episodes of etching and resorption. Extensive development of hexagonal and trigonal etch pits resulted from the action of oxidizing CO?-H?O fluids, and some late-stage etching is believed to have occurred in the hypabyssal dyke system prior to kimberlite eruption.